2007
DOI: 10.3163/1536-5050.95.4.381
|View full text |Cite
|
Sign up to set email alerts
|

Decreased hospital length of stay associated with presentation of cases at morning report with librarian support

Abstract: Presentation of a case at MR, followed by the timely dissemination of the results of an online literature review, resulted in a shortened LOS and lower hospital charges compared with controls. MR, in association with a computerized literature search guided by the librarians, was an effective means for introducing evidence-based medicine into patient care practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 22 publications
1
52
0
1
Order By: Relevance
“…The decisions made for the last night patients are usually discussed in the Socratic manner. Presentation of cases at morning report sessions results in a significant shortened length of stay confirmed in several studies [8,11]. Multiple studies have shown, the morning report case presentation with focused questions, has got numerous advantages including shorter duration of admission, clarifying the complicated cases [12], diagnosis change and covering educational objectives [13].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The decisions made for the last night patients are usually discussed in the Socratic manner. Presentation of cases at morning report sessions results in a significant shortened length of stay confirmed in several studies [8,11]. Multiple studies have shown, the morning report case presentation with focused questions, has got numerous advantages including shorter duration of admission, clarifying the complicated cases [12], diagnosis change and covering educational objectives [13].…”
Section: Discussionmentioning
confidence: 94%
“…Introducing the status of new patients in educational sessions result in a thoughtful challenge of critical thinking and decision-making [6,7]. Studies have shown that proper and systematic presentation of cases lead to reduced patient`s length of stay in the hospital and costs [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single study assessed whether incorporating evidence-based medicine in morning report affected patient outcomes, and it found reduced length of stay and lower median hospital charges for patients whose cases had been discussed at morning report. 8 Our study has limitations. First, the survey was mainly distributed to the residents and did not include attending or clinical fellows.…”
Section: Discussionmentioning
confidence: 99%
“…2 A growing body of evidence has underscored the need to advocate for EBM training in residencies. [3][4][5][6][7][8] Teaching with an EBM approach facilitates development of the skills needed to bring the most current information to the realtime practice of medicine and has led for calls to ensure principles of EBM, including biostatistics, critical appraisal and medical informatics, are included into graduate medical education programs. 9 In most residency programs, this training has traditionally been relegated to journal clubs, in which small group discussions focus on articles chosen for their relevance to a particular specialty and several survey studies have shown that these learning venues are most commonly employed.…”
Section: Introductionmentioning
confidence: 99%